DETEKSI LEMAK BABI PADA BEBERAPA PRODUK LIPSTIK CAIR IMPOR MENGGUNAKAN SPEKTROFOTOMETER FTIR UNTUK ANALISIS KEHALALAN - Syamsuri Syakri (Jurnal Kesehatan, 2019)
A study entitled detection of Pig Fat in Several Imported Liquid Lipsticks Using FTIR Spectrophotometry for. The purpose of this study was to identify pork fat in imported liquid lipstick products using the FTIR Spectrophotometer method, and to conduct a qualitative analysis of pork fat in imported liquid lipstick products using the FTIR Spectrophotometer method. The method used in this study is a qualitative analysis method, for the working procedure begins with the sampling process using a sample of 3 imported liquid lipsticks originating from Korea, Thailand, and China, then extracting oil on product samples, and testing using a spectrophotometer FTIR. After the results are obtained, the FTIR Spectrum Data Interpretation is performed. From these results it was found that the FTIR Spectrophotometer Method can be used to identify lard in imported liquid lipstick products. Based on the results of the comparison of the results of the interpretation of the data of Sample 1, Sample 2 and Sample 3 with the spectra data of pork fat from the journal Hermanto, it can be concluded that Sample 1 and Sample 3 have functional groups that are similar to the interpretation of data from the spectrum of lard in several studies on fat pig. However, if seen from the spectrum, there is a difference between Sample 1, Sample 2 and Sample 3 with the spectrum of lard from the journal. Further research needs to be done using other instruments to ensure the presence of lard content in Sample 1, Sample 2 and Sample 3.